Perancangan Lampu Menggunakan Konsep Internet of Thing (IoT) Berbasis Microcontroller - Chalista Dwi Maharani; Jimmie Jimmie; Zulhipni Reno Saputra Elsi (LPPM Universitas Sains dan Teknologi Komputer, 2026)
The rapid advancement of the Internet of Things (IoT) has spurred the development of intelligent home systems that optimize energy use and enhance user convenience. One essential component of a smart home environment is an adaptive lighting system that can operate based on environmental conditions. This study aims to design and implement a microcontroller-based automatic lighting system that responds to variations in ambient light intensity and supports further integration with IoT-based monitoring. The system is built using an Arduino Atmega328P microcontroller, a Light Dependent Resistor (LDR) sensor for illumination detection, and a relay module to control the electrical load. This research employs an experimental design that includes system analysis, hardware assembly, software development, and performance testing. The LDR sensor was tested under bright and dark conditions, producing consistent readings, with an average threshold of 450–500 analog units for light and below 300 units for dark. The system successfully activated the lamp in 100% of dark-condition trials (n=10) and turned it off correctly in all bright-condition trials (n=10). Response time measurements showed that the system processed changes in light intensity in less than 1 second, ensuring real-time adaptability. The findings demonstrate that the proposed design operates reliably, optimizes electricity usage, and reduces the need for manual intervention. This study contributes to the development of affordable, energy-efficient, innovative lighting systems. It provides a practical foundation for future work, including full IoT integration with wireless modules for remote control and monitoring.